MASH [videorecording (DVD)] - Altman, Robert, 1925-2006; Sutherland, Donald, 1935-; Gould, Elliott; Skerritt, Tom; Kellerman, Sally; Duvall, Robert; Auberjonois, René, 1940-2019-; Hooker, Richard (Twentieth Century Fox Home Entertainment, 2004)
Three Korean War Army surgeons adopt a hilarious, lunatic lifestyle as an antidote to the tragedies of their Mobile Army Surgical Hospital.